Is there a relationship between the overhead press and split jerk maximum performance? Influence of sex - Soriano, M. A.; Haff, G. G.; Comfort, P.; Amaro-Gahete, F. J.; Torres-González, A.; García-Cifo, A.; Jiménez-Ormeño, E.; de Baranda, P. S. (International Journal of Sports Science & Coaching, 2022)
The aims of this study were to (I) determine the differences and relationship between the overhead press and split jerk performance in athletes involved in weightlifting training, and (II) explore the magnitude of these differences in one-repetition maximum (1RM) performances between sexes. Sixty-one men (age: 30.4 ± 6.7 years; height: 1.8 ± 0.5 m; body mass 82.5 ± 8.5 kg; weightlifting training experience: 3.7 ± 3.5 yrs) and 21 women (age: 29.5 ± 5.2 yrs; height: 1.7 ± 0.5 m; body mass: 62.6 ± 5.7 kg; weightlifting training experience: 3.0 ± 1.5 yrs) participated. The 1RM performance of the overhead press and split jerk were assessed for all participants, with the overhead press assessed on two occasions to determine between-session reliability. The intraclass correlation coefficients (ICC) and 95% confidence intervals showed a high reliability for the overhead press ICC = 0.98 (0.97-0.99). A very strong correlation and significant differences were found between the overhead press and split jerk 1RM performances for all participants (r = 0.90 [0.93 0.85], 60.2 ± 18.3 kg, 95.7 ± 29.3 kg, p = 0.001). Men demonstrated stronger correlations between the overhead press and split jerk 1RM performances (r = 0.83 [0.73-0.90], p = 0.001) compared with women (r = 0.56 [0.17-0.80], p = 0.008). These results provide evidence that 1RM performance of the overhead press and split jerk performance are highly related, highlighting the importance of upper-limb strength in the split jerk maximum performance.